In silico analysis of Trisindoline 1 compound against Mpro SARS-CoV-2 as novel potential drugs candidate - Fitri Lianingsih (Universitas Mataram, 2021)
The novel coronavirus 2019 (SARS-CoV-2) is one of the viruses that can infect humans and cause high mortality worldwide. The protease (Mpro) is key SARS-CoV-2 an enzyme mediates the viral replication and the transcription. Mpro is currently used as the candidate for the SARS-CoV-2 vaccine because Mpro is one of the key enzymes in the viral life cycle that essential for interactions between the virus and host cell receptor during viral entry. The Mpro can be a target protein to design the novel drug of SARS-CoV-2. The drug design from natural products that are considered to have low toxicity is needed against the virus. The study aims to determines the potential pharmacology of Trisindoline 1 compound from the sponge Hyrtios altum against SARS-CoV-2 and to find the amino acid residues between interaction ligand-protein receptors. The methods of this study use the virtual screening of Auto Dock Vina and visualization the amino acid residue using Bio via Discovery Studio. The result of this study was the selected marine compound from Trisindoline 1 may have potential to developed as inhibitor of SARS-CoV-2.Keywords: In Silico, Mpro, Sars Cov 2, Trisindoline 1, Sponges